PEMERIKSAAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KPP KEPANJEN KABUPATEN MALANG - Pujo Gunarso (Jurnal Keuangan dan Perbankan, 2016)
This study was conducted in 2015 on the territory of the Tax Office Primary Kepanjen region. The purpose of this study is to examine the effect of tax audits and tax penalties for mandatory compliance body. Method and data analysis which was used in this research was multiple linear regression analysis, the statistical test that consists of the calculation of validity, reliability, classical assumptions, regression, coefficient of determina-tion and hypothesis testing. The results indicates that the examination of the tax and tax penalties have significant impact on taxpayer compliance. Based on these results, audits and tax sanctions can improve taxpayer compliance behavior of the body. The results support Ebimoboweis (2013), Durans (2009) and Nugrohos (2006), but the results are not suitable with Winerungans (2012) and Princes (2014).